Citrus in the world - García-Figuera, Sara; Coletta-Filho, Helvécio D.; Vicent, Antonio; Drenth, André; Hendrick, Paul; Zhou, Changyong (ISSP, 2022)
This report provides an assessment of citrus health globally. Citrus trees are a perennial crop grown for its fruits, which are one of the key sources of vitamin C in human diets (Liu et al 2012), a source of simple sugars, dietary fibre and secondary metabolites (Lv et al 2015), and a key ingredient in juices, jams, jellies and marmalades. Citrus fruits and by-products from juice production are also used to extract essential oils and citric acids used in the food, cosmetics and pharmaceutical industries (Kaur et al 2021; Panwar et al 2021). It is estimated that around 2/3 of citrus fruits produced worldwide are consumed as fresh fruit, and the remaining 1/3 is used mainly for juice production and some industrial purposes (Liu et al 2012).